Quantification of respiratory parameters in patients with temporal lobe epilepsy Quantificação de parâmetros respiratórios em pacientes com epilepsia do lobo temporal - Fulvio Alexandre Scorza; Ana Maria Fonseca Abreu; Marly de Albuquerque; Julio B Cota Pacheco; Renato Breviglieri; Josemir Wanderley Sander; Antônio Carlos da Silva; Esper Abrão Cavalheiro; Ricardo Mario Arida (Arquivos de Neuro-Psiquiatria)
Dysfunction affecting cardiac or pulmonary systems has been postulated as a major factor in sudden death in epilepsy (SUDEP). Whilst the majority of studies of cardiorespiratory function have focused on changes during seizures, here we investigate whether epilepsy influences basal respiratory parameters in patients with temporal lobe epilepsy (TLE) during the interictal period. Spirometry was performed in 10 females and 10 males. Measurements of Vital Capacity (VC), Forced Vital Capacity (FVC), Forced Expiratory Volume in the first second (FEV1) and ratios of FEV1 to FVC (FEV1/FVC) were obtained, and these values were analyzed as percentages of predicted values. None of the patients had chronic obstructive pulmonary disease and no significant alterations in respiratory function tests were found among these patients. No association between seizure frequency, antiepileptic drugs and SUDEP could be found in this study. Although the study did not identify any specific respiratory abnormality in TLE patients during the interictal period, re-evaluation of clinical data on pulmonary disorders in people with epilepsy should be better investigated. Alterações cardíacas e pulmonares têm sido propostas como principais fatores de risco no fenômeno da morte súbita em epilepsia (SUDEP). Enquanto a maioria dos estudos tem verificado as alterações da função cardiorrespiratória durante as crises epilépticas, nosso estudo avaliou a função pulmonar de indivíduos com epilepsia do lobo temporal (ELT) no período interictal. Vinte pacientes com ELT (10 homens e 10 mulheres) participaram de nosso estudo. Nos testes de função pulmonar foram mensurados os seguintes parâmetros: Capacidade Vital Forçada (CVF), Capacidade Vital Lenta (CVL), Volume Expiratório Forçado no primeiro segundo (VEF1) e o Índice VEF1/CVF. Os resultados foram comparados aos valores de normalidade preditos na literatura. Nenhum dos pacientes apresentou doença pulmonar obstrutiva ou restritiva e alterações significativas nos testes de função pulmonar. Não foram encontradas associações entre a freqüência de crises, drogas antiepilépticas e SUDEP. Embora nosso estudo não tenha identificado qualquer anormalidade respiratória específica em indivíduos com ELT durante o período interictal, os dados clínicos sobre transtornos pulmonares em indivíduos com epilepsia devem ser melhor avaliados.